USE OF DESIGN OF EXPERIMENTS TO OPTIMISE THE ENVIRONMENTAL PERFORMANCE OF CONSUMER PRODUCTS: A CASE STUDY OF SHOWERS AND TAPWARE IN NEW ZEALAND. (May 2020) - Horrell, M.; Shekar, A.; McLaren, S.
Abstract: Eco-tools and techniques often lack guidance and a robust methodology for improving the environmental performance of products with an active use phase. A case study was undertaken to investigate the role of Design of Experiments (DoE) in providing insights to improve the environmental performance of two product categories with active use phases: showers and tapware. The results show how varying the components can reduce energy use and demonstrated how DoE can be used as an objective method for optimising a products environmental performance when user behaviour can influence the results.